2010
DOI: 10.1080/14681991003747430
|View full text |Cite
|
Sign up to set email alerts
|

Adult male rape and sexual assault: prevalence, re-victimisation and the tonic immobility response

Abstract: Fifteen years ago we summarised research on what was known about the sexual assault of men and its effects. Here we present evidence from epidemiological research that demonstrates that the sexual assault of men is observed in many countries -demonstrating the widespread existence of the sexual assault of men and the need for further research. We also present research to show that the association between child sexual abuse and sexual assault in adult females has also been found in a variety of studies on men. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Rape myth acceptance -the extent to which a person adheres to such beliefs -is substantial in members of the general public (between 19% and 57%;Sussenbach & Bohner, 2011). Furthermore, whilst it is true that a number of rape myths also exist regarding male victims (Coxell & King, 2010;Davies & Rogers, 2006), this paper focuses on male-on-female rape, and rape myth beliefs regarding female victims and male perpetrators.…”
Section: Introductionmentioning
confidence: 97%
“…Rape myth acceptance -the extent to which a person adheres to such beliefs -is substantial in members of the general public (between 19% and 57%;Sussenbach & Bohner, 2011). Furthermore, whilst it is true that a number of rape myths also exist regarding male victims (Coxell & King, 2010;Davies & Rogers, 2006), this paper focuses on male-on-female rape, and rape myth beliefs regarding female victims and male perpetrators.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, due to a lack of participation from individuals who identify outside the gender binary (i.e., do not identify as a woman or as a man), this population was excluded from the analysis to avoid bias. The survey drew from the Canadian Criminal Code (Statistics Canada, 2008) and from the literature (McMahon, 2011;Coxell & King, 2010;Harrell et al, 2009;Rape, Abuse & Incest National Network, 2009;Busch-Armendariz, DiNitto, Bell, & Bohman, 2010) to define sexual assault as unwanted sexual contact, including, but not limited to unwanted touching, kissing, or penetration.…”
Section: Methodsmentioning
confidence: 99%
“…indicate that their literature review found that "two of three individuals who are sexually victimized will be revictimized" (p. 103). Coxell and King (2010) report that the same seems to hold true in what limited data are available concerning male victims, citing evidence that "men who have experienced child sexual abuse are more likely to report" sexual assault (p. 373). Finkelhor and Browne (1985) describe a process by which sexual abuse survivors may be placed at greater risk for sexual traumas in the future, known as the process of "traumatic sexualization," a "process in which a child's sexuality (including both sexual feelings and attitudes) is shaped in a developmentally inappropriate and interpersonally dysfunctional fashion as a result of sexual abuse" (p.…”
Section: Sexual Assault Literaturementioning
confidence: 95%
“…Tonic immobility is not well studied. The literature that is available concerning the TI has established the phenomenon as a theoretical construct and provided anecdotal data supporting it Burgess & Holmstrom, 1976;Coxell & King, 2010;Galliano, Noble, Travis & Peuchl, 1993;. However, establishing TI as a known human response to terror, and describing the phenomenon as it is experienced by survivors, remain important tasks, as the ability to accurately understand and describe the nature and meaning of the phenomenon to its survivors is the first step towards accurately identifying, diagnosing and treating the sequelae of such a response.…”
Section: Need For Studymentioning
confidence: 99%